Long-acting injectable second-generation antipsychotics in first-episode psychosis: a narrative review. (March 2019) - Salgueiro, Monika; Segarra, Rafael
Abstract : Long-acting injectable (LAI) antipsychotics could be a favorable option of treatment and have some advantages over oral medications. The aim of this study was to review the published data on the use of LAI formulation of second-generation antipsychotics (SGA) in first-episode psychosis (FEP). Using PubMed and Scopus databases, we performed a systematic literature search of articles published between 1 January 2000 and 30 April 2018, that reported clinical trials on the use of LAI SGAs in patients with FEP. Seventy-seven articles were considered eligible and full-text revised. Five studies fulfilled the inclusion criteria and evaluated the effect of LAI risperidone in FEP patients. Treatment with LAI SGAs was well accepted, and the majority of FEP patients agreed to change from an oral to an injectable formulation. At the 12-month follow-up, between 68 and 95% of FEP patients treated with LAI risperidone showed a good clinical response and 64% achieved remission of symptoms for at least 24 months of follow-up. Treatment with LAI SGAs can offer significant advantages over oral antipsychotics to FEP patients, especially to improve the adherence to medication and prevent the worsening of symptoms, the relapse, and rehospitalization associated with the discontinuation of treatment.